The bhūtasaṃkhyā notation: numbers, culture, and language in Sanskrit mathematical literature - Petrocchi, A (Institute of Buddhist Studies and BDK America, Inc., 2017)
A method of expressing numbers by means of symbolic words arranged as in place value notation was developed in India in the early centuries of the Common Era. In the bhūtasaṃkhyā notation, the digits from 0 to 9 are denoted by certain significant words that connote a numerical association derived from many areas of Indian culture. This paper analyzes this system, taking into account the relation between mathematical representations, culture, and language that contribute to its originality. While looking at the bhūtasaṃkhyā as the creative attainment of a process in which the flexibility of the Sanskrit language has been used as a tool that functions in poetic structure and the method of oral transmission of Sanskrit mathematical texts, I argue that it also represents a “constitutively social form” of language, where each sign, embedded in social images, memories, and descriptive information, becomes mathematical “sense-making,” insofar it is rooted in the semantic field “Indian culture.” In order to understand cognitive and social functions served by this numerical notation system, I attempt to delineate, with the use of a formalized language typical of mathematical logic, the dialectic between numbers and collective representations in the context of ancient Indian culture.